Effectiveness of Mindfulness-Based Group Counseling to Reduce Loneliness in Adolescents Victims of Bullying - Safira, Chandra Ayu; Izzaty, Rita Eka (Buletin Konseling Inovatif, 2025)
This research proceeds from the problems of loneliness experienced by most adolescent victims of bullying. Mindfulness is recommended as an effective way to alleviate the problem, but some school counselors have not integrated mindfulness in guidance and counseling services. Therefore, this study aimed to test the effectiveness of mindfulness-based group counseling services to reduce loneliness in adolescent victims of bullying. This quantitative research uses a quasi-experimental type with a non-equivalent control group design. The research location was at State High School 11 and 9 Yogyakarta-Indonesia, involving 20 students aged 15-18 years who were selected with purposive sampling techniques. Data were collected using the UCLA Loneliness Scale version 3 with Cronbach alpha reliability 0.906. The scale has been tested for content validity by expert judgment. Data were analyzed using the statistical Wilcoxon Signed Ranks Test and the Mann Whitney test. The research results showed that there was a significant difference between the pretest and posttest results in the experimental group. Significant differences were also seen in the comparison of the experimental and control groups. This means that mindfulness-based group counseling services are effective in reducing loneliness in adolescent victims of bullying. School counselors should consider integrating mindfulness-based group counseling into their programs, especially for students who have experienced bullying. These services can help students develop skills to reduce feelings of loneliness by fostering relationships with peers who have similar experiences.